(untitled) (Bangladesh Journal of Medical Biochemistry, 2025)
Metabolic syndrome is a cluster of conditions including central obesity, high blood pressure, high blood sugar, and dyslipidemia which collectively heighten the risk of cardiovascular diseases and type 2 diabetes. Thyroid stimulating hormone, a pivotal regulator of thyroid gland activity, plays a crucial role in maintaining overall metabolic homeostasis. This study was conducted to investigate and establish the correlation between thyroid stimulating hormone (TSH) levels and the various components of metabolic syndrome in type 2 diabetic patients. This observational study was conducted in a tertiary care hospital, from July 2014 to June 2015. A total 200 subjects were selected with the age range from 18 to 70 years meeting the International Diabetic Federation criteria for metabolic syndrome and not on any medications. Baseline assessments of demographic data, physical examinations, and measurements such as body weight, height, BMI, waist circumference, blood pressure, FBG, total cholesterol, triglycerides, HDL-C, and TSH levels were done. Correlation between variables were determined by Pearson’s correlation coefficient with significance set at P<0.05. This study shows BMI, waist circumference (WC), SBP, total cholesterol (TC), triglycerides (TG), and FBS exhibited a significant positive linear correlation (P<0.05) with thyroid stimulating hormone (TSH) levels. Conversely, age and high-density lipoprotein cholesterol (HDL-C) displayed a non-significant negative correlation (P>0.05) with TSH levels. This study revealed significant associations between TSH levels and metabolic syndrome, emphasizing a potential link between thyroid function and metabolic health. These findings underscore the importance of considering thyroid function in the assessment and management of metabolic disorders. However, further research is warranted to establish causation and elucidate the underlying mechanisms of this association. Bangladesh J Med Biochem 2020; 13(1): 05-10